Effect of carbonated water on cerebral blood flow in the frontal region: a study using near-infrared spectroscopy - Kosugi, Wataru; Sumali, Brian; Hamada, Nozomu; Mitsukura, Yasue (Frontiers in Behavioral Neuroscience, 2024)
Introduction: Carbonated water (CarbW) affects the swallowing function associated with the action of the brainstem. In addition, CarbW ingestion promotes mean blood flow in the middle cerebral artery, which is associated with blood flow to the frontal and temporal lobes. In this milieu, studies regarding the effect of drinking CarbW on brain activity are of significance. In the present study, we compared the changes in cerebral blood flow in the frontal region before and after the ingestion of CarbW or uncarbonated water (SW). Methods: Near-infrared spectroscopy was used to continuously measure the cerebral blood flow at 22 channels in the frontal region of 13 healthy young adults for 10 min before and after the ingestion of CarbW or SW. We statistically compared the changes in oxyhemoglobin concentration before and after the ingestion of CarbW or SW. Results: Compared with that before CarbW ingestion, the oxyhemoglobin concentration in the left frontal region increase after CarbW ingestion. In particular, a significant increase (p < 0.05) was observed in the ch21 region. On the contrary, no marked increase or decrease in cerebral blood flow was observed after SW ingestion compared with that before ingestion. Discussion: The activated part of the frontal region (ch21) corresponds to the vicinity of the orbitofrontal cortex, which is reportedly activated by rewarding stimuli. In addition, as the orbitofrontal cortex is located at the terminal end of the reward pathway of the mesocortical system, CarbW ingestion might have acted on the dopaminergic reward pathway of the mesocortical system.